High-adhesion perfluoroether rubber / metal composite part as well as preparation method and application thereof
Through sandblasting and plasma functional treatment, the metal surface characteristics are improved, combined with the adhesive layer and vulcanization process, the problem of difficulty in compositeing between perfluoroether rubber and metal is solved, and perfluoroether rubber with high bond strength and chemical corrosion resistance is achieved /Metal composite parts.
Patent Information
- Application Number
- CN202411663910.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-07
AI Technical Summary
It is difficult to recombine with metals, resulting in poor sealing performance and bonding strength, which makes it difficult to meet the sealing needs in the chemical industry.
The surface roughness and activity of metals are improved by sandblasting and plasma functionalization, combined with an appropriate amount of adhesive layer and an optimized vulcanization process, a high-adhesive perfluoroether rubber/metal composite product is prepared.
It significantly improves the bonding strength and chemical corrosion resistance of perfluoroether rubber to metals, meeting the sealing and transportation needs in the chemical industry.
Smart Images

Figure CN119391015A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber composite material processing, and in particular to a high-adhesive perfluoroether rubber / metal composite product and a preparation method and application thereof. Background Art
[0002] Chemical delivery systems are an indispensable part of the modern chemical industry and are widely used in chemical plants, pharmaceutical plants, laboratories, etc. Accidents such as leakage and explosion may occur during chemical delivery. Therefore, it is extremely important to ensure the sealing of the transport device during the delivery process and the stability of the long-term operation of the equipment.
[0003] Fluororubber (FKM) has excellent chemical corrosion resistance and high temperature resistance, and is widely used in the field of industrial sealing. FKM can be used in harsh environments with strong acids, strong alkalis and other media, and has good sealing performance. In practical applications in the chemical industry, it is often necessary to compound fluororubber with metal parts, but because the CC bonds of FKM are surrounded by a large number of fluorine atoms, its surface energy is low, which makes it difficult to compound FKM with metals. Perfluoroether rubber (FFKM) does not contain CH structure, and compared with FKM, it is more difficult to compound FFKM with metals. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, an embodiment of the present invention provides a highly adhesive perfluoroether rubber / metal composite part and a preparation method and application thereof.
[0006] In the first aspect, the present invention provides a method for preparing a highly adhesive perfluoroether rubber / metal composite component, such as Figure 1 As shown, the following steps are included:
[0007] (a) Sandblasting of metal parts;
[0008] (b) treating the sandblasted metal part with an organic solvent and drying it, then performing plasma functionalization treatment on its surface, and after cooling to room temperature, coating an adhesive layer on the surface of the metal part and pre-curing it to obtain a pre-cured metal part;
[0009] (c) taking a perfluoroether raw rubber with a corresponding Mooney value, adding an auxiliary agent while refining, and mixing evenly to obtain a sheet-like mixed rubber;
[0010] (d) preheating the precured metal part in a mold, adding the mixed rubber, performing two vulcanization processes, and cooling the temperature to room temperature to obtain a perfluoroether rubber / metal composite part.
[0011] Furthermore, the metal part includes one of aluminum, copper, stainless steel, iron and zinc.
[0012] Furthermore, the sandblasting material of the sandblasting treatment includes one or more of quartz sand, glass sand, aluminum sand, steel shot, and silicon carbide.
[0013] Furthermore, the sand granules of the sandblasting material have a mesh size of 20 to 80. Spraying sand granules of a suitable mesh size on the surface of the metal part can increase the contact area and roughness of the surface of the metal part, thereby facilitating the subsequent interface wetting between the metal part and the adhesive.
[0014] Sand particles of appropriate size enhance the bonding strength of composite parts. When the sand particles are too large, the metal surface roughness is too large, which can easily cause deformation of metal parts during processing, making it difficult for the adhesive to flow or requiring a thicker adhesive layer. When the sand particles are too small, the riveting effect between the interfaces is reduced, which is detrimental to the bonding effect.
[0015] Furthermore, the organic solvent treatment in step (b) is to immerse the sandblasted metal parts in an organic solvent, reflux, and ultrasonically clean them for 1 to 10 hours at 40 to 80°C. The purpose of treating the sandblasted metal parts with organic solvents is to degrease the metal surface and perform functional modification at the same time. Fluorine-containing solvents can also attach fluorine-containing groups to the metal surface, which is beneficial to the bonding of FFKM to the metal. At a suitable temperature, the metal surface is completely degreased, and there are more fluorine-containing groups. When the temperature is too low, the grease on the metal surface cannot be completely removed, affecting the subsequent bonding; when the temperature is too high, the solvent evaporates faster and the surface active groups are less.
[0016] Furthermore, the organic solvent includes one or more of ethanol, ethyl acetate, isopropanol, dichloromethane, perfluoromethylcyclohexane, tetrafluoropropanol, perfluorohexane, and perfluorocyclohexane.
[0017] Furthermore, the gas atmosphere of the plasma functionalization treatment in step (b) includes one of argon, nitrogen, oxygen, fluorine and air. The purpose of plasma treatment is to activate the metal surface, so that the surface has active functional groups and enhance the bonding strength of the composite parts.
[0018] Furthermore, the treatment time of the plasma functionalization treatment in step (b) is 10 to 300 seconds.
[0019] Furthermore, the thickness of the adhesive layer in step (b) is 0.1 to 0.5 mm.
[0020] Furthermore, the adhesive includes one of silane coupling agents, fluorine-containing silane coupling agents, epoxy resins, and modified hot melt adhesives.
[0021] The purpose of coating adhesive on the surface of metal parts is to bond metal and FFKM. Appropriate adhesive thickness makes the bonding strength between metal and FFKM higher. When the thickness of adhesive is too large, the cost will increase, and it is easy to shrink unevenly, which will affect the bonding effect. When the thickness of adhesive is too small, it is easy to have problems such as hollowing and falling off, resulting in uneven bonding strength of parts.
[0022] Furthermore, the pre-curing in step (b) is to keep warm at 100-200°C for 10-120 minutes. The role of pre-curing is to ensure that the adhesive itself has a certain strength before being composited with the rubber for vulcanization, so as to prevent the adhesive from being impacted by the high-temperature and high-pressure rubber material during the vulcanization process of the composite part, thereby damaging the adhesive layer. Pre-curing at a suitable pre-curing temperature and time can improve production efficiency, reduce the internal stress concentration of the adhesive, and facilitate bonding. If the temperature is too high, the curing speed of the adhesive is fast and internal stress is easily formed; if the time is too long, the curing degree is too high, which affects the further action of the adhesive and FFKM; if the temperature is too low, the curing speed is slow, which affects the efficiency; if the time is too short, the curing degree is low, and it is difficult to maintain the stability of the adhesive layer, thereby affecting the final bonding effect.
[0023] Furthermore, the Mooney value of the perfluoroether rubber is 10 to 80MU. The perfluoroether rubber with a suitable Mooney value makes the composite parts have better processing and molding performance. When the Mooney value of the perfluoroether rubber is too large, the flow performance of the rubber is poor, and higher temperature and pressure are required to increase the flow performance of the rubber to ensure the diffusion effect of the rubber on the surface of the adhesive. High temperature and high pressure are easy to cause premature vulcanization of the rubber, thereby affecting the mechanical properties and bonding effect of the rubber itself; when the Mooney value of the perfluoroether rubber is too small, the strength of the rubber itself is low, which is not conducive to the later use of the composite parts.
[0024] Further, the auxiliary agent includes 0.5 to 5 parts of a vulcanization auxiliary agent, 0.5 to 5 parts of a cross-linking auxiliary agent, 5 to 50 parts of a filler, 0 to 5 parts of a fluorine-containing auxiliary agent, and 0 to 5 parts of a processing auxiliary agent, wherein the vulcanization auxiliary agent includes one of dibenzoyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-bishexane, and 2,4-di-tert-butyl peroxide isopropyl benzene; the cross-linking auxiliary agent includes one or more of triallyl isocyanurate, triallyl cyanurate, and fluorinated diene; the filler includes one or more of carbon black, silicon dioxide, barium sulfate, titanium dioxide, zinc oxide, glass beads, and calcium carbonate; and the fluorine-containing auxiliary agent includes one or more of trifluoropropyl methyldimethoxysilane, perfluorooctanamide propyl triethoxysilane, and heptadecafluorodecyl trimethoxysilane.
[0025] Among them, the role of the vulcanization aid is to initiate rubber vulcanization and shorten the vulcanization time; the role of the cross-linking aid is to increase the cross-linking density of the rubber and improve the mechanical properties of the material; the role of the filler is to reinforce the rubber and adjust the performance and cost of the mixed rubber; the role of the processing aid is to provide internal and external lubrication during the processing process, appropriately increase the fluidity of the rubber, and reduce the sticking phenomenon. The processing aid is one of the commercially available processing aids WS280, HT290, and GW-40004500200.
[0026] Further, the two vulcanizations in step (d) are divided into the first vulcanization and the second vulcanization, wherein the first vulcanization is to keep warm for 5 to 60 minutes at 120 to 200°C, and the second vulcanization is to keep warm for 1 to 24 hours at 200 to 250°C. After the precured metal parts are placed in the mold for preheating, the purpose of preheating is to enhance the activity of the adhesive layer so that it can quickly interact with the FFKM rubber compound after contact, and synchronize with the rubber vulcanization; add the FFKM rubber compound for the first vulcanization, and after the first vulcanization is completed, the second vulcanization is carried out, and after the second vulcanization is completed and cooled to room temperature, a metal / perfluoroether rubber composite part is obtained. Among them, the specific preheating process is to put the metal parts into the mold, close the mold and preheat for 15 minutes, the amount of FFKM rubber compound added is determined according to the size of the mold, and an appropriate amount of FFKM rubber compound is added to fill the entire mold. The vulcanization is divided into two times to make the vulcanization and cross-linking of the fluororubber more complete, and the volatile substances generated during the rubber vulcanization process can be further removed, so as to obtain a rubber part with excellent performance and stability.
[0027] During the vulcanization process, under the appropriate vulcanization temperature and time conditions, the rubber can be completely vulcanized and the composite parts can be easily prepared; if the vulcanization temperature is too high and the vulcanization speed is too fast, on the one hand, the rubber part itself is prone to stress concentration or stratification, and on the other hand, it is not conducive to the interaction with the adhesive layer; if the vulcanization time is too long, it will cause over-vulcanization of the rubber, which will reduce the rubber performance; if the vulcanization temperature is too low, on the one hand, the vulcanization speed of the rubber is slow, affecting the efficiency, and on the other hand, the interaction speed between the rubber and the adhesive is also slowed down, affecting the bonding effect; when the time is too short, the rubber is not completely vulcanized, affecting the rubber performance.
[0028] In a second aspect, the present invention provides a highly adhesive perfluoroether rubber / metal composite part prepared by the method proposed in the first aspect.
[0029] In a third aspect, the present invention proposes the use of the high-adhesion perfluoroether rubber / metal composite product prepared by the method proposed in the first aspect or the high-adhesion perfluoroether rubber / metal composite product proposed in the second aspect in a chemical delivery system.
[0030] Compared with the prior art, the beneficial effects of the present invention are:
[0031] The present invention structurally and functionally modifies the metal surface through multiple composite processes, and optimizes and regulates the fluidity and vulcanization characteristics of the FFKM compound rubber through formula and process, so that the prepared FFKM / metal composite parts have both high bonding strength and excellent chemical corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0033] Figure 1 The present invention is a flow chart of the method for preparing a highly adhesive perfluoroether rubber / metal composite product. DETAILED DESCRIPTION
[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0035] The present invention is specifically described below in conjunction with embodiments.
[0036] Example 1
[0037] S1: sandblasting the surface of a metal part, wherein the metal part is stainless steel and the sandblasting material is 40 mesh aluminum sand.
[0038] S2: At 40°C, the sandblasted metal parts were immersed in a mixture of ethanol and perfluorohexane in a volume ratio of 1:1, refluxed, and ultrasonicated for 1 hour. After drying, the surface of the metal parts was plasma functionalized for 10 seconds. After cooling to room temperature, the adhesive with a thickness of 0.1 mm was quickly and evenly applied on the surface of the metal parts, and cured at 100°C for 10 minutes. The plasma atmosphere was air, and the adhesive was silane adhesive.
[0039] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 20, add 2 parts of vulcanization aid 2,5-dimethyl-2,5-bishexane, 3 parts of cross-linking agent TAIC, and 15 parts of filler carbon black while refining, mix evenly and then produce sheets to obtain a mixed rubber.
[0040] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 120°C for 60 minutes, and the second vulcanization is kept at 200°C for 24 hours.
[0041] Example 2
[0042] S1: performing sandblasting on the surface of a metal part, wherein the metal part is stainless steel and the sandblasting material is 40-mesh quartz sand.
[0043] S2: At 40°C, the sandblasted metal parts were immersed in ethyl acetate, refluxed, and ultrasonicated for 10 hours. After drying, the surface of the metal parts was plasma functionalized for 50 seconds. After cooling to room temperature, the adhesive was quickly and evenly coated on the surface of the metal parts with a thickness of 0.2 mm, and cured at 150°C for 10 minutes. The plasma atmosphere was argon and the adhesive was perfluorodecyltrimethoxysilane.
[0044] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 30, add 5 parts of vulcanizing aid 2,5-dimethyl-2,5-bishexane, 3 parts of cross-linking aid triallyl cyanurate, 5 parts of filler silica, 5 parts of fluorine-containing aid trifluoropropylmethyldimethoxysilane, and 2 parts of processing aid WS280 while refining, mix evenly and then sheet out to obtain a mixed rubber.
[0045] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 200°C for 5 minutes, and the second vulcanization is kept at 220°C for 16 hours.
[0046] Example 3
[0047] S1: performing sandblasting on the surface of a metal part, wherein the metal part is iron and the sandblasting material is 20 mesh aluminum sand.
[0048] S2: At 40°C, the sandblasted metal parts were immersed in isopropanol, refluxed, and ultrasonicated for 6 hours. After drying, the surface of the metal parts was plasma functionalized for 100 seconds. After cooling to room temperature, the adhesive with a thickness of 0.3 mm was quickly and evenly applied on the surface of the metal parts, and cured at 200°C for 10 minutes. The plasma atmosphere was nitrogen and the adhesive was epoxy resin.
[0049] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 50, add 0.5 parts of vulcanization aid dibenzoyl peroxide, 3 parts of cross-linking aid fluorinated diene, 50 parts of filler barium sulfate, 2 parts of fluorine-containing aid trifluoropropylmethyldimethoxysilane, and 3 parts of processing aid HT290 while refining, mix evenly and then sheet out to obtain a mixed rubber.
[0050] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 150°C for 40 minutes, and the second vulcanization is kept at 200°C for 24 hours.
[0051] Example 4
[0052] S1: sandblasting the surface of a metal part, wherein the metal part is stainless steel and the sandblasting material is 80 mesh aluminum sand.
[0053] S2: At 50°C, the sandblasted metal parts were immersed in dichloromethane, refluxed, and ultrasonicated for 5 hours. After drying, the surface of the metal parts was plasma functionalized for 200 seconds. After cooling to room temperature, the adhesive with a thickness of 0.4 mm was quickly and evenly applied on the surface of the metal parts, and cured at 100°C for 50 minutes. The plasma atmosphere was fluorine gas, and the adhesive was a modified hot melt adhesive.
[0054] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 70, add 2 parts of vulcanization aid diisopropylbenzene peroxide, 5 parts of cross-linking agent TAIC, 20 parts of filler titanium dioxide, 3 parts of fluorine-containing additive heptadecafluorodecyltrimethoxysilane, and 3 parts of processing aid GW-40004500200 while refining, mix evenly and then sheet out to obtain a mixed rubber.
[0055] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 180°C for 20 minutes, and the second vulcanization is kept at 250°C for 1 hour.
[0056] Example 5
[0057] S1: performing sandblasting on the surface of a metal part, wherein the metal part is copper and the sandblasting material is 40-mesh glass sand.
[0058] S2: At 80°C, the sandblasted metal parts were immersed in perfluoromethylcyclohexane, refluxed, and ultrasonicated for 1 hour. After drying, the surface of the metal parts was plasma functionalized for 300 seconds. After cooling to room temperature, the adhesive with a thickness of 0.5 mm was quickly and evenly applied on the surface of the metal parts, and cured at 100°C for 100 minutes. The plasma atmosphere was air, and the adhesive was perfluorodecyl trimethoxy.
[0059] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 80, add 2 parts of vulcanization aid 2,4-di-tert-butyl peroxide isopropylbenzene, 0.5 parts of cross-linking agent TAIC, 30 parts of filler zinc oxide, 5 parts of fluorine-containing additive perfluorooctylamide propyl triethoxysilane, and 5 parts of processing aid WS280 while refining, mix evenly and then sheet out to obtain a mixed rubber.
[0060] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 150°C for 40 minutes, and the second vulcanization is kept at 230°C for 10 hours.
[0061] Example 6
[0062] S1: performing sandblasting on the surface of a metal part, wherein the metal part is zinc and the sandblasting material is 40 mesh silicon carbide.
[0063] S2: At 80°C, the sandblasted metal parts were immersed in tetrafluoropropanol, refluxed, and ultrasonicated for 4 hours. After drying, the surface of the metal parts was plasma functionalized for 150 seconds. After cooling to room temperature, the adhesive was quickly and evenly coated on the surface of the metal parts with a thickness of 0.5 mm, and cured at 100°C for 120 minutes. The plasma atmosphere was oxygen, and the adhesive was a silane adhesive / perfluorodecyl and trimethoxysilane with a volume ratio of 1:1.
[0064] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 60, add 2 parts of vulcanization aid 2,5-dimethyl-2,5-bishexane, 3 parts of cross-linking agent TAIC, 15 parts of filler glass microspheres, 5 parts of fluorine-containing additive heptadecafluorodecyltrimethoxysilane, and 5 parts of processing aid HT290 while refining, mix evenly and then sheet out to obtain a mixed rubber.
[0065] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 180°C for 20 minutes, and the second vulcanization is kept at 220°C for 16 hours.
[0066] Example 7
[0067] S1: performing sandblasting on the surface of a metal part, wherein the metal part is aluminum and the sandblasting material is 40 mesh aluminum sand.
[0068] S2: At 80°C, the sandblasted metal parts were immersed in perfluorohexane, refluxed, and ultrasonicated for 10 hours. After drying, the surface of the metal parts was plasma functionalized for 30 seconds. After cooling to room temperature, a 0.4 mm thick adhesive was quickly and evenly applied on the surface of the metal parts, and cured at 120°C for 50 minutes. The plasma atmosphere was oxygen, and the adhesive was a silane adhesive.
[0069] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 40, add 2 parts of vulcanization aid 2,5-dimethyl-2,5-bishexane, 3 parts of cross-linking agent TAIC, 50 parts of filler calcium carbonate, and 3 parts of fluorine-containing additive trifluoropropylmethyldimethoxysilane while refining, mix evenly and then produce sheets to obtain a mixed rubber.
[0070] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 200°C for 5 minutes, and the second vulcanization is kept at 230°C for 10 hours.
[0071] Example 8
[0072] S1: sandblasting the surface of a metal part, wherein the metal part is stainless steel and the sandblasting material is 40 mesh steel shot.
[0073] S2: At 50°C, the sandblasted metal parts were immersed in perfluorocyclohexane, refluxed, and ultrasonicated for 7 hours. After drying, the surface of the metal parts was plasma functionalized for 200 seconds. After cooling to room temperature, the adhesive with a thickness of 0.3 mm was quickly and evenly applied on the surface of the metal parts, and cured at 140°C for 120 minutes. The plasma atmosphere was air, and the adhesive was silane adhesive.
[0074] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 80, add 2 parts of vulcanization aid 2,5-dimethyl-2,5-bishexane, 3 parts of cross-linking agent TAIC, 5 parts of filler carbon black, and 5 parts of processing aid HT290 while refining, mix evenly and then sheet out to obtain a mixed rubber.
[0075] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 120°C for 60 minutes, and the second vulcanization is kept at 230°C for 10 hours.
[0076] Example 9
[0077] S1: sandblasting the surface of a metal part, wherein the metal part is stainless steel and the sandblasting material is 80 mesh aluminum sand.
[0078] S2: At 50°C, the sandblasted metal parts were immersed in a mixture of ethanol and perfluorohexane in a volume ratio of 1:1, refluxed, and ultrasonicated for 10 hours. After drying, the surface of the metal parts was plasma functionalized for 80 seconds. After cooling to room temperature, a 0.2 mm thick adhesive was quickly and evenly applied on the surface of the metal parts, and cured at 200°C for 120 minutes. The plasma atmosphere was air, and the adhesive was a silane adhesive.
[0079] S3: Take 100 parts of perfluoroether raw rubber with a Mooney value of 20, add 2 parts of vulcanization aid 2,5-dimethyl-2,5-bishexane, 3 parts of cross-linking agent TAIC, 30 parts of filler carbon black, and 5 parts of processing aid GW-40004500200 while refining, mix evenly and then sheet out to obtain a mixed rubber.
[0080] S4: Preheat the preheated metal part in the mold, then add FFKM to fill the mold, perform the first vulcanization and the second vulcanization, after the two vulcanizations are completed, cool to room temperature to obtain a metal / perfluoroether rubber part. The first vulcanization is kept at 120°C for 60 minutes, and the second vulcanization is kept at 230°C for 10 hours.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that the surface of the metal part is not subjected to plasma treatment.
[0083] Comparative Example 2
[0084] The difference from Example 2 is that the surface of the metal part is not subjected to sandblasting.
[0085] Comparative Example 3
[0086] The difference from Example 3 is that the sandblasting material is 100 mesh aluminum sand.
[0087] The perfluoroether rubber / metal composite parts obtained in Examples 1 to 9 and Comparative Examples 1 to 3 were subjected to peel strength tests, and the test method was based on GB / T 15254-2014 "180° Peel Test for Vulcanized Rubber and Metal Bonding". The test results are shown in Table 1 below.
[0088] Table 1:
[0089] Grouping Peel strength Example 1 9N / cm Example 2 8N / cm Example 3 7N / cm Example 4 8N / cm Example 5 7N / cm Example 6 6N / cm Example 7 8N / cm Example 8 9N / cm Example 9 8N / cm Comparative Example 1 2N / cm Comparative Example 2 1N / cm Comparative Example 3 3N / cm
[0090] From Table 1, we can see that:
[0091] The peel strength of the composite products prepared in Examples 1 to 9 is greater than that in Examples 1 to 3;
[0092] By comparing Example 1 with Comparative Example 1, it can be seen that when no plasma treatment is performed, the peel strength of the prepared composite product is reduced, and the plasma surface treatment can make the metal surface have active functional groups so as to improve the bonding strength of the composite product;
[0093] By comparing Example 2 with Comparative Example 2 and Comparative Example 3, it can be seen that when the surface of the metal part is not sandblasted or the sandblasting particle size is too large, the peel strength of the prepared composite part is reduced. Sandblasting effectively improves the bonding strength between FFKM and metal, but too large a particle size is not conducive to the preparation of composite parts.
[0094] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0095] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0096] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a highly adhesive perfluoroether rubber / metal composite part, characterized in that: The following steps are involved: (a) Sandblasting of metal parts; (b) treating the sandblasted metal part with an organic solvent and drying it, then performing plasma functionalization treatment on its surface, and after cooling to room temperature, coating an adhesive layer on the surface of the metal part and pre-curing it to obtain a pre-cured metal part; (c) taking a perfluoroether raw rubber with a corresponding Mooney value, adding an auxiliary agent while refining, and mixing evenly to obtain a sheet-like mixed rubber; (d) preheating the precured metal part in a mold, adding the mixed rubber, performing two vulcanization processes, and cooling the temperature to room temperature to obtain a perfluoroether rubber / metal composite part.
2. The method according to claim 1, characterized in that The metal part includes one of aluminum, copper, stainless steel, iron and zinc; And / or, the sandblasting material for the sandblasting treatment includes one or more of quartz sand, glass sand, aluminum sand, steel shot, and silicon carbide; And / or, the sand granules of the sandblasting material have a mesh size of 20 to 80.
3. The method according to claim 1, characterized in that The organic solvent treatment in step (b) is to immerse the sandblasted metal part in an organic solvent at 40 to 80° C., reflux, and ultrasonically clean it for 1 to 10 hours; And / or, the organic solvent includes one or more of ethanol, ethyl acetate, isopropanol, dichloromethane, perfluoromethylcyclohexane, tetrafluoropropanol, perfluorohexane, and perfluorocyclohexane; And / or, the gas atmosphere of the plasma functionalization treatment in step (b) comprises one of argon, nitrogen, oxygen, fluorine and air; And / or, the treatment time of the plasma functionalization treatment in step (b) is 10 to 300 seconds.
4. The method according to claim 1, characterized in that The thickness of the adhesive layer in step (b) is 0.1 to 0.5 mm; And / or, wherein the adhesive includes one of silane coupling agents, fluorine-containing silane coupling agents, epoxy resins, and modified hot melt adhesives.
5. The method according to claim 1, characterized in that The pre-curing in step (b) is performed by keeping the temperature at 100-200° C. for 10-120 minutes.
6. The method according to claim 1, characterized in that The Mooney value of the perfluoroether raw rubber is 10 to 80 MU.
7. The method according to claim 1, characterized in that The auxiliary agent includes 0.5 to 5 parts of a vulcanization auxiliary agent, 0.5 to 5 parts of a cross-linking auxiliary agent, 5 to 50 parts of a filler, 0 to 5 parts of a fluorine-containing auxiliary agent, and 0 to 5 parts of a processing auxiliary agent, wherein the vulcanization auxiliary agent includes one of dibenzoyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-bishexane, and 2,4-di-tert-butyl peroxide isopropyl benzene; the cross-linking auxiliary agent includes one or more of triallyl isocyanurate, triallyl cyanurate, and fluorinated diene; the filler includes one or more of carbon black, silicon dioxide, barium sulfate, titanium dioxide, zinc oxide, glass microbeads, and calcium carbonate; and the fluorine-containing auxiliary agent includes one or more of trifluoropropyl methyldimethoxysilane, perfluorooctanamide propyl triethoxysilane, and heptadecafluorodecyl trimethoxysilane.
8. The method according to claim 1, characterized in that The two vulcanizations in step (d) are divided into a first vulcanization and a second vulcanization, wherein the first vulcanization is carried out at 120-200° C. for 5-60 minutes, and the second vulcanization is carried out at 200-250° C. for 1-24 hours.
9. A highly adhesive perfluoroether rubber / metal composite part, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the highly adhesive perfluoroether rubber / metal composite article prepared by the method according to any one of claims 1 to 8 or the highly adhesive perfluoroether rubber / metal composite article according to claim 9 in a chemical delivery system.
Citation Information
Cited By
Perfluoroether rubber adhesive and preparation method thereof
CN120536103A
Perfluoroether rubber valve plate and preparation method thereof
CN121200271A
Perfluoroether rubber valve plate and method of making
CN121200271B